INTERPERSONAL VIOLENCE IN A TRADITIONAL SOCIETY. FORMS OF AGGRESSION AND SOCIAL CONTROL IN CHILE. XIX CENTURY - Salinas Meza, René (Revista de Historia Social y de las Mentalidades, 2025)
this article examines the interpersonal violence like a daily facet of the chilean society of 19th century. in this century, the violence was not a penalized conduct and was a cross-sectional idea to all the groups and social spaces and were expressed from the domestic violence to rural banditry characteristic of 19th century, being used like as a mean of resolution of conflicts or strategy to survival and to like a reinfor - cing of the masculinity. in addition, the violence was legitimized by the courts, who emphasized the necessity to punish conducts considered transgressions, before to distribute justice. the violence also was facilitated by the bad conditions of life of the chilean villages of 19th century and thigh social confliction, exceeding the effectiveness of the state codes of control of the violence through its judicial organisms.